Tutoring – Institualization of New Profession in Russian School - Ковалева, Татьяна (Educological discourse, 2014)
The article describes the principle of openness as a qualitative characteristic of modern Russian education, historical facts about the phenomenon tutoring are presented. Author pays much attention to open educational technologies and tutor practices, explains the legal aspects of the registration of the tutor activity at the school.